2019
DOI: 10.1111/vco.12482
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of three‐dimensional canine osteosarcoma cell lines showing vasculogenic mimicry and evaluation of biological properties after treatment with 17‐AAG

Abstract: Vasculogenic mimicry (VM) is an alternative type of blood perfusion characterized by formation of non‐endothelial cell‐lined microcirculatory channels and is responsible for aggressive tumour biology and increased tumour‐related mortality. VM‐correlated genes are associated with vascular endothelial grown factor receptor 1 (VEGFR1), and hypoxia‐related (hypoxia inducible factor 1 α—HIF1α) signalling pathways, whose molecules are client proteins of Hsp90 (heat shock protein 90) and are potential therapeutic tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
(100 reference statements)
1
10
0
Order By: Relevance
“…The generation of a hypoxia compartment induced the production of VEGF factor by tumour cells promoting proliferation and differentiation of HUVEC to produce vascular tubule-like structures. Using dog OS cell lines (D22 and D17) and 3D collagen gels, Massimini et al demonstrated that a non-human OS model was associated with induced vasculogenic mimicry and that 17-AAg drug abolished tumour progression and micro vascular channel formation [110] .…”
Section: D Culture Methods Of Primary Bone Tumoursmentioning
confidence: 99%
“…The generation of a hypoxia compartment induced the production of VEGF factor by tumour cells promoting proliferation and differentiation of HUVEC to produce vascular tubule-like structures. Using dog OS cell lines (D22 and D17) and 3D collagen gels, Massimini et al demonstrated that a non-human OS model was associated with induced vasculogenic mimicry and that 17-AAg drug abolished tumour progression and micro vascular channel formation [110] .…”
Section: D Culture Methods Of Primary Bone Tumoursmentioning
confidence: 99%
“…OS tumors appear to develop such an endothelial-free tumor-derived vasculogenic network, as vascular mimicry is found in 22.7% of osteoblastic-type OS samples and associated with unfavorable prognostis [104,105]. Human OS cell lines (U2OS [106], MG-63 [105]) and aggressive canine cell lines [107] are able to form vessel-like structures in three-dimensional cultures. Vascular mimicry mechanisms remain largely unknown, often being assessed via inappropriate and biased in vitro assays [108].…”
Section: Neo-vascularization In Osmentioning
confidence: 99%
“…As far as VEGF/VEGFR axis in veterinary oncology is concerned, VEGF family members were identified in several canine cancers ( 76 ), as well as OSA tissue, serum, and cultured cells ( 77 – 79 ). A relation between VM and VERGFR was found in D17 canine OSA cells cultured on type I collagen where malignant cancer cells with endothelial morphology express VEGFR1 ( 14 ). Correlation between VM and VEGF axis has been firstly investigated in dogs with mammary tumors ( 7 ).…”
Section: Endothelial Mediatorsmentioning
confidence: 99%
“…Moreover, canine inflammatory mammary carcinomas were analyzed for the presence of VM by transmission and scanning electron microscopy ( 13 ). In addition, as far as canine OSA is concerned, the presence of vessel-like structures in a long-term canine D17 OSA cell cultured on type I collagen has been recently described ( 14 ). As well, treatment with the heat shock protein 90 (Hsp90) inhibitor 17-N-allylamino-17-demethoxygeldanamycin (17-AAG) inhibited the migration of D17 OSA cells, also decreasing VM markers in vitro and inducing a reduction of hypoxia-inducible factor 1α (HIF1α) transcript and protein expression ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation